Factors Related to Diabetic Distress in Diabetes Mellitus Patients - Fitrina, yossi; Srywahyuni, Ade; Putra, Abdi Setia; Yani, Zahra Fitri; J, Junios (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Diabetes distress if left untreated will often persist and develop into more severe conditions such as depression, sleep disturbances and increased risk of suicide. The study aims to identify factors related to diabetes distress in people with diabetes melitus in work area of the Kampung Teleng Health Centre, Sawahlunto City in 2024. The study used a quantitative method with correlative descriptive research design and a sampel size of 126 respondents. The sampling technique use was purpossive sampling and quota sampling technique. The variable studied were powerlessness, negative social perceptions, family distress, hypoglicaemia distress, management distress, eating distress as dependent variables and diabetes distress as independent variables. Data collection using the DDS-17, PAT, GAD-7, HDFSS, HFS-II, PAID, dan DEPS-R questionnaires. Data processing using the spearman rank test. The result of the study showed the factors related to diabetes distress were negative social perceptions with p value (a) = 0,007 and correlation (r) = 0,241 and hypoglicemia distress with p value (a) = 0,049 and correlation (r) = 0,176. The conclusion of this study shows that factors related to diabetes distress are negative social perceptions and hypoglicemia distress. It is expected that the Kampung Teleng Health Center in Sawahlunto City can develop a program to preverent diabetes distress with health service, espicially doctors, so that they can provide direction, advice, respond to concerns from diabets melitus suffers and provide education about the impact of diabetes distress